If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(u-1)-1=-5(-6u+2)-9u
We move all terms to the left:
5(u-1)-1-(-5(-6u+2)-9u)=0
We multiply parentheses
5u-(-5(-6u+2)-9u)-5-1=0
We calculate terms in parentheses: -(-5(-6u+2)-9u), so:We add all the numbers together, and all the variables
-5(-6u+2)-9u
We add all the numbers together, and all the variables
-9u-5(-6u+2)
We multiply parentheses
-9u+30u-10
We add all the numbers together, and all the variables
21u-10
Back to the equation:
-(21u-10)
5u-(21u-10)-6=0
We get rid of parentheses
5u-21u+10-6=0
We add all the numbers together, and all the variables
-16u+4=0
We move all terms containing u to the left, all other terms to the right
-16u=-4
u=-4/-16
u=1/4
| 9u+36=7(u+4) | | -4n+15-5n+7=n-43 | | -16=-6w+2(w+6) | | .8x=65+.7x | | 20+.07x=36.5+.04x | | 0.3x+8=8.25 | | 10.5x=19+5.75x | | 0.3x8=8.25 | | 6w+2w+10=180 | | 44+.4x=30+.6x | | 4c+160=7c+70 | | -13=5(+4m)-2m | | m4+4m³+8m²-8m+4=0 | | X*x²=0 | | 0.0625+7x=49.62500 | | 2w^2-3w-527=0 | | 3a+2=1/4 | | 2m+16=24 | | 2x+0.875=8.87500 | | 16-2r=-36+6r+1 | | 4x^2+15x−4=0 | | 4(3a+2)^2+15(3a+2)−4=0 | | 3a=-7/4 | | x2-4/7x=16/49 | | 5p=6(6p+7) | | 0.24y-20.9=0.14y | | 90=0.1x | | 5.1x-4=4.1 | | d^2+5=0 | | 10(z+2)-3(z-3)=3(z-2)+3(z-1) | | -0.25+6x+(-0.75)x=-0.25 | | -w+210=46 |